2001
DOI: 10.2208/prohe.45.211
|View full text |Cite
|
Sign up to set email alerts
|

Matsuyama City Rainfall Data Analysis Using Wavelet Transform

Abstract: An application of wavelet analysis is done with the total monthly rainfall data of Matsuyama city, in order to analyze the rainfall variability observed in such an area. Besides the rainfall variability analysis, the main frequency components in the time series are studied by the global wavelet spectrum, revealing that the monthly rainfall in Matsuyama city is composed mainly by an annual frequency. Thus, the modulation in the 8-16-month band is examined by an average of all scales between 8 and 16 months,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 7 publications
0
42
0
Order By: Relevance
“…w 0 must be equal to or greater than 5 to satisfy the wavelet admissibility condition (Farge, 1992;Cromwell, 2001): the function must have zero mean and be localized in both time and frequency space to be "admissible" as a wavelet (Santos et al, 2001). In the present application, we use w 0 = 6, a value commonly used for geoscience applications Compo, 1998, Labat, 2005;Si and Zeleke, 2005;Schaefli and Zehe, 2009).…”
Section: Wavelet Transform Analyses On Water-level Time Seriesmentioning
confidence: 99%
“…w 0 must be equal to or greater than 5 to satisfy the wavelet admissibility condition (Farge, 1992;Cromwell, 2001): the function must have zero mean and be localized in both time and frequency space to be "admissible" as a wavelet (Santos et al, 2001). In the present application, we use w 0 = 6, a value commonly used for geoscience applications Compo, 1998, Labat, 2005;Si and Zeleke, 2005;Schaefli and Zehe, 2009).…”
Section: Wavelet Transform Analyses On Water-level Time Seriesmentioning
confidence: 99%
“…Wavelet analysis has advantage over other methods since it is able to identify temporal variability in the periodic nature of the time series as shown by Refs. [6,15,16]. While spectral analysis reduces information to ensemble averages, wavelet analysis technique categorizes the information in terms of time-frequency modes, decomposing the signals into localized oscillations and achievable through isolating short processes embedded in highly structured harmonic phenomena, analyze the progression of time signals or track the characteristics of an event or feature over a wide range of scales.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5] have suggested that interannual variability of the oceanic stratification could modulate the SST signature of the MJO (Madden Jullien Oscillation) and may be both high and low frequency oscillations associated with MJO itself. Santos, C. A. G. et al [6] used wavelet transform using rainfall time series for studies concerning soil erosion and land degradation for runoff-erosion simulations.…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem Wavelet Transform can be used, which transformed or decomposed a one dimensional time series into two diffusive time series simultaneously. Only then it is possible to get information from any periodic signals within the time series and how this time series varies over time [17].…”
Section: Datamentioning
confidence: 99%